MINIATUR SISTEM KONTROLER ESKALATOR OTOMATIS MENGGUNAKAN ARDUINO - john ohoiwutun; Sonny Rumalutur; Kasmi Edy (LPPM Poltek ST Paul, 2019)
Escalators or walking stairs are very important for buildings that have more than one or two floors, because if people are going up or down from one floor to another floor is very troublesome and of course it will take a lot of energy when using ordinary stairs. With the escalator or the stairs running is expected to help people to make effective the energy used. Besides that people will not feel tired if you have to go up and down stairs. However, with the development of technology nowadays, ordinary existing escalators are considered to be less efficient, because the escalators continue to work even though the escalators are not used. If this is allowed to continue continuously it is very inefficient and certainly wasteful of energy (electricity). The effect of this waste will not only be felt by the building owner but indirectly can also be felt by the wider community who still need a lot of electrical energy seen from the amount of electricity used to run the escalator stairs.